Relatório final do estágio curricular obrigatório do curso de medicina veterinária, realizado junto à Ad’oro, São Carlos, São Paulo: Coccidiose, programas de monitoria e controle da doença - Costa, Miguel Zanetti da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Widespread in poultry farming worldwide, coccidiosis is a pathogen caused by a protozoan of the genus Eimeria spp. which affects the intestine of birds, causing enteritis and diarrhea in the most severe cases, reducing the animals' metabolic and immunological efficiency. It is estimated that adding costs with prevention, control, mortality, morbidity and decreased performance, the Brazilian market has an annual loss of six billion reais due to the disease. This report describes the locations and activities carried out during the Curricular Internship in a Veterinary Clinic, which was developed together with the Research and Development team at A'doro, São Carlos - SP. In addition, you will also find a literary review on coccidiosis and content on monitoring, prevention and control of the disease.
Final report of the mandatory curricular internship of the veterinary medicine course, carried out at Ad’oro, São Carlos, São Paulo: Coccidiosis, disease monitoring and control programs
Keywords: Avicultura; Aves domésticas doenças; Coccidiose em aves